INTERFERENSI BAHASA DAERAH TERHADAP BAHASA INDONESIA LISAN MASYARAKAT KABUPATEN SERANG PROVINSI BANTEN - Asep Muhyidin (Jurnal Membaca Bahasa dan Sastra Indonesia, 2016)
This research is intended to find out the process of interference mother language on the the use of Indonesia language orally in Serang society Banten province. The research methode used in this research is descriptive kualitative. The objective of the research is to describe sistematically the process of interference in Serang regency on Indonesia language used by socety in Serang Regency as the bilingual speaker. The result of the research shown that interference existed on lexical feature, morphology and syntax.